Kuat Tekan Self-Healing Concrete Berbasis Enkapsulasi Xanthan Gum - Hafizh, Muhammad; Mauludin, Luthfi Muhammad; Keryanti, Keryanti; Susanto, Ambar (Borneo Engineering : Jurnal Teknik Sipil, 2024)
This study aims to determine the reaction and performance of self-healing concrete using Bacillus megaterium encapsulation with xanthan gum coating through a simple extrusion method. The focus of the study is on the effect of adding xanthan gum microcapsules on the compressive strength of concrete and determining the optimal microcapsule content. The percentage of xanthan gum microcapsules used is 1,2,3,4, and 5%. Based on the test results, the addition of 2% xanthan gum microcapsules provides the highest compressive strength, which is 25.6 MPa on the 7th day and 34.1 MPa on the 28th day. Further test results show that although the addition of 5% microcapsules provides the greatest strength return, the use of higher amounts of microcapsules actually reduces the overall concrete strength. Therefore, the optimal microcapsule content to be added to the concrete mixture is 2%, which provides the best balance between increasing strength and material stability.